Two-dimensional numerical modeling for separation of deformable cells using dielectrophoresis - Ye, Ting (2014)
In this paper, we numerically explore the possibility of separating two groups of deformable cells, by a very small dielectrophoretic (DEP) microchip with the characteristic length of several cell diameters. A 2D two-fluid model is developed to describe the separation process, where three types of forces are considered, the aggregation force for cell–cell interaction, the deformation force for cell deformation, and the DEP force for cell dielectrophoresis. As a model validation, we calculate the levitation height of a cell subject to DEP force, and compare it with the experimental data. After that, we simulate the separation of two groups of cells with different dielectric properties at high and low frequencies, respectively. The simulation results show that the deformable cells can be separated successfully by a very small DEP microchip, according to not only their different permittivities at the high frequency, but also their different conductivities at the low frequency. In addition, both two groups of cells have a shape deformation from an original shape to a lopsided slipper shape during the separation process. It is found that the cell motion is mainly determined by the DEP force arising from the electric field, causing the cells to deviate from the centerline of microchannel. However, the cell deformation is mainly determined by the deformation force arising from the fluid flow, causing the deviated cells to undergo an asymmetric motion with the deformation of slipper shape.